Burden of Human Papilloma Virus Infection and Related Comorbidities in Men: Implications for Research, Disease Prevention and Health Promotion among Hispanic Men - Colón-López, Vivian; Ortiz, Ana P.; Palefsky, Joel (Puerto Rico Health Sciences Journal, 2010)
Genital Human papillomavirus (HPV) infection is one of the most commonly diagnosed sexually transmitted infections world-wide. Over the last two decades, research has established a strong causal link between specific types of HPV infection and cancer, particularly cervical, anal, vulval/vaginal, penile, and oropharyngeal cancer. Limited epidemiological studies of anogenital HPV infection have been conducted in Hispanic populations (including Puerto Rico), and population-based incidence and prevalence estimates of HPV infection among Hispanics are limited. Studies which evaluate knowledge and awareness of HPV among men are also scarce. With the world-wide introduction of two new prophylactic vaccines against high-risk HPVs causing cervical cancer, and the recent FDA approval of one of them in preventing genital warts in men, there is an urgency to determine the burden of HPV in Hispanic populations before vaccine programs are implemented on a widespread basis. Knowledge and acceptability of the vaccine prior to implementation of these programs are also necessary to allow a targeted assessment. This review article summarizes existing research literature on HPV infection and HPV related morbidities in men, with a particular emphasis on Hispanic men in the United States and Puerto Rico. Three mayor areas are discussed: (1) genital warts, (2) HPV and related cancers and (3) biobehavioral and psychosocial factors related to HPV infection and vaccination. Specific recommendations for advancing HPV research and knowledge among Hispanic populations are also suggested.